MScanFit motor unit number estimation (MScan) and muscle velocity recovery cycle recordings in amyotrophic lateral sclerosis patients. Issue 8 (August 2019) - Kristensen, R.S.; Bostock, H.; Tan, S.V.; Witt, A.; Fuglsang-Frederiksen, A.; Qerama, E.; Andersen, H.; Tankisi, H.
Highlights: Detailed CMAP scans and MVRCs were recorded in 26 patients with ALS. MScan revealed marked motor unit loss. MVRCs were largely unchanged, suggesting successful reinnervation of muscle fibres. Abstract: Objective: Motor Unit Number Estimation (MUNE) methods, such as the recently developed MScanFit MUNE (MScan), may be valuable in tracking motor unit loss in ALS. Muscle Velocity Recovery Cycles (MVRCs) provide information about muscle membrane properties and can reveal disease-related changes. This study was undertaken to test the applicability of MScan to the anterior tibial muscle (TA) and to test whether the MVRCs could improve understanding of ALS pathophysiology. Methods: Twenty-six ALS patients and 25 healthy controls were evaluated by quantitative electromyography, nerve conduction study and the two novel methods: MScan and MVRC; all in the TA and peroneal nerve. Results: The estimated number of motor units for ALS patients (Median: 45, interquartile range: 28.5–76.5) was significantly lower than for the controls (117, 96.0–121.0) (P = 2.19 × 10 −7 ). Unit size was increased only when amplitudes were expressed as percentage of CMAP. Of MVRC measurements, only relative refractory period was significantly abnormal in patients. Conclusion: MScanFit MUNE gives a sensitive and quantitative measure of loss of TA motor units in ALS. Muscle fiber membrane properties are mostly unaffected, despite substantial denervation, presumably due to collateral reinnervation. Significance: MScan is suitable for detecting motor unit loss in TA. MVRCs do not provide new insights in ALS.